Consent of the State to Arbitration with Foreign Investor – Modes of Consent, Restrictions and Applicable Law - Đundić, Petar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Consent of states to resolve disputes with foreign investors through investment arbitration is connected with certain distinctive characteristics, most of which result out of the peculiar character of the state as a sovereign entity. Those characteristics concern instruments containing consent as well as various restrictions brought upon the jurisdiction of the arbitral tribunal in cases in which it might seem obvious that consent exists. The paper represents an overview of the methods for expressing consent by the statesand conditions to which it is subjected. Furthermore, a significant attention is devoted to the problem of designating the rules applicable to the interpretation of instruments potentially containing consent of the state.